AQUIFER CHARACTERIZATION USING VERTICAL ELECTRICAL SOUNDING IN AUCHI POLYTECHNIC, AUCHI, EDO STATE, NIGERIA. (Nigerian Journal of Technology, 2020)
The Schlumberger array method was used to carry out a total of eight (8) Vertical Electrical Sounding (VES) with a spread of 350 m in the study area. The Pasi 16-GL Terrameter was used to acquire the data. The data obtained were analyzed with the Winresist 1.0 software to obtain the curves of best fit to the theoretical models. The modeling program converted the apparent resistivity into true resistivity values in 1-D model curves. Five (5) to seven (7) layers were delineated which correspond to the topsoil, sandy clay, clayey sand, sand, dry sandstone and saturated sandstone. The depth to aquifer ranges from 95.0 to 169.6 m with resistivity values ranging from 324.3 to 1524.7 ?m.   http://dx.doi.org/10.4314/njt.v39i3.35